Effect of magnetic field tapering on whistler pumped free electron laser - Kumara, Manish (American Institute of Physics Inc., 2019)
An analytical formalism of whistler pumped free electron laser (FEL) with tapered magnetic field is developed. The tapering raises the efficiency of the device to 7% for typical parameters. The frequency and power of the FEL can be controlled by tuning the plasma density and/or magnetic field also by increasing the energy of electron beam. The angle of injection of electron beam is very crucial for higher efficiency of FEL. Presence of plasma ensures the space charge and current neutralization and larger power handling capacity of the device.
Keywords: Electron beams; Free electron lasers; Magnetic fields; Magnetoplasma; Plasma density; Pumping (laser)